2022
DOI: 10.1016/j.diabres.2021.109063
|View full text |Cite
|
Sign up to set email alerts
|

Screening, diagnosis and management of diabetic sensorimotor polyneuropathy in clinical practice: International expert consensus recommendations

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
125
0
21

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(147 citation statements)
references
References 164 publications
(194 reference statements)
1
125
0
21
Order By: Relevance
“…Previous studies link neuropathic pain with interference with daily activities [28,29]. Others relate neuropathic pain with a disability, quality of life and psychosocial impairment [30,31]. Other studies, however, have indicated that pain may be associated with poor quality of life [32] while others also have reported that symptoms of pain may be associated with reduced well-being or quality of life [33].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies link neuropathic pain with interference with daily activities [28,29]. Others relate neuropathic pain with a disability, quality of life and psychosocial impairment [30,31]. Other studies, however, have indicated that pain may be associated with poor quality of life [32] while others also have reported that symptoms of pain may be associated with reduced well-being or quality of life [33].…”
Section: Discussionmentioning
confidence: 99%
“…A second limitation is the clinical diagnosis of DSPN. Indeed, we did not use more sophisticated modalities, such as nerve conduction velocity, intraepidermal nerve fibre density via skin biopsy, or corneal confocal microscopy, which may enable earlier diagnosis of subclinical DSPN [ 1 , 2 , 29 ]. Moreover, subjects were included in a tertiary care centre, and so results may not be directly applicable to primary care and/or the general T2DM population.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic neuropathy remains a major chronic complication of diabetes mellitus [ 1 ]. It may, in turn, lead to further complications, notably diabetic foot, neuropathic pain, and autonomic failure [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Benfotiamin proved its beneficial effects in type 2 DM patients in regards to vascular function in terms of restoring reactive hyperaemia and laboratory parameters of endothelial function if given in advance of an AGE-rich meal [ 31 ]. In addition, Benfotiamin is a licensed drug and approved for the treatment of diabetic polyneuropathy (DPN) in several countries worldwide [ 32 ], and its use in symptomatic DPN is recommended [ 33 ]. Still, new substances are under clinical evaluation [ 34 ].…”
Section: Therapeutic Possibilitiesmentioning
confidence: 99%